The review of stock returns and macroeconomic variables - Ali, Umar Ahmad; Abdullah, Adam; Sulong, Zunaidah; Ahmad, Tijjani Abdullahi (Human Resource Management Academic Research Society, 2015)
This study aims to review a number of studies on stock market returns and macroeconomic variables. The reviewed literature are categorised into three groups: literature related to developed countries, literature related to developing countries, and literature related to group countries. Moreover, the various empirical studies reviewed show mixed results and conclusions. In some studies, strong positive relationships are found to exist between stock returns and macroeconomic fundamentals and in some the relationship is a bit weak. Other researches report different results. This mixture of findings and conclusions emanates from differences in methodology, variables used and the period of study. There is also disparity in study area that fundamentally affects the behaviour of the macroeconomic variables.